THE INFLUENCE OF CURRENT RATIO, DEBT TO EQUITY RATIO, AND NET PROFIT MARGIN ON LQ45 STOCK RETURN IN THE INDONESIA STOCK EXCHANGE - Sombolayuk, Wihalminus (Contemporary Journal on Business and Accounting, 2023)
ABSTRACT Purpose – This study aims to find the effect of current ratio, debt to equity ratio ang net profit margin on LQ45 stock return on the Indonesia Stock Exchange. Design/methodology/approach – This study uses a quantitative paradigm with a deductive approach. Findings – The results of the study show the company's liquidity, which is proportional to the current ratio, has a positive and significant effect on company stock returns in the LQ 45 Index. The solvency of the company proxied by the debt-to-equity ratio has a positive and significant effect on the company's stock return in the LQ 45 Index. Profitability proxied by the net profit margin has a positive but not significant effect on company stock returns in the LQ 45 Index Liquidity, solvency and profitability have a significant effect on changes in stock returns. Originality – The population in this study are all issuers registered with LQ 45 from 2013 -2017 Keywords: Current Ratio, Debt to Equity Ratio, Net Profit Magin Ratio Paper Type Research Result